The global playbook for tobacco control policy: Challenges, strategies, and a case study from Malaysia - Tien Jack How; Jyh Ye Shim; Mohd Azizan Abdullah; Zulhilmi Ahmad Zulkepli; Sandra Lydia Lucius; Abdul Rahman Ramdzan; Kamal Kasra (Penerbit Universiti Malaysia Sabah, 2025)
Tobacco use remains a leading cause of preventable death globally, disproportionately affecting low-and middle-income countries (LMICs). Despite the implementation of the WHO MPOWER strategy, significant challenges persist, including the high prevalence of smoking among lower socioeconomic groups and the rapid emergence of e-cigarettes, particularly among youth. This narrative review explores the contemporary challenges in tobacco control, outlines effective strategies, and analyzes Malaysia's policy alignment with global recommendations to guide future interventions. A literature search was conducted in May 2025 across the Scopus, PubMed, and Cochrane Central databases. The search focused on articles published in English within the last 15 years, using keywords related to the challenges (e.g., "policy resistance," "enforcement problems") and strategies (e.g., "taxation," "cessation programme") of tobacco and e-cigarette control policy. All study designs were considered, while editorials and presentations were excluded. The review identifies two primary areas. First, key challenges to tobacco control include significant socioeconomic disparities in nicotine dependence, aggressive marketing targeting vulnerable populations, regulatory gaps concerning synthetic nicotine and novel products, and industry interference through legal challenges and manipulation of international trade policies. Second, effective strategies are categorized across three levels: macro (comprehensive taxation, product regulation), meso (community-based initiatives, pictorial health warnings), and micro (individual-level interventions like incentive programs and pharmacological support). Effective tobacco control demands a multi-layered, equitable approach that integrates robust policy with community and individual support. By enacting the Control of Smoking Products for Public Health Act, Malaysia has taken a positive step, but further action is crucial. Key future priorities include: 1) enhancing and harmonizing fiscal and legal measures through international collaboration to prevent industry forum-shopping; 2) sustaining investment in public education to reduce initiation and normalize cessation; and 3) advancing targeted research on cessation supports, especially for LMICs.